MOTIVASI BERPRESTASI PEMAIN SEPAKBOLA JUNIOR SSB PERISAI KOTA PAYAKUMBUH - Masrun; Rifano Adiza; Yanuar Kiram; Roma Irawan (Fakultas Ilmu Keolahragaan Unimed, 2026)
This study aims to determine the relationship between achievement motivation and the performance of soccer players at SSB Perisai in Payakumbuh. This study employs a quantitative descriptive approach using a correlational method. The study population consisted of 35 players, with a sample of 20 selected using purposive sampling. The instrument used was a achievement motivation questionnaire with a Likert scale covering aspects of intrinsic and extrinsic motivation. Data analysis techniques included the Liliefors normality test and product-moment correlation analysis. The results indicate a significant relationship between achievement motivation and player performance, with a correlation coefficient of 0.781—greater than the critical value of 0.444 at a significance level of α = 0.05. This suggests that the higher a player’s achievement motivation, the better their performance. Thus, achievement motivation plays a crucial role in enhancing soccer players’ performance.